Implications of western culture hybridation in Indonesia through KFC (Kentucky Fried Chicken) - Adiba, Wardah Fara (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
This research seeks to analyze the influence of westernization that is spreading in Indonesian culture. Globalization has had a huge influence on culture in Indonesia, the progress of globalization has made the westernization process easier due to the reduction of time and place constraints in relations between countries. One of them is the United States using globalization as a tool to spread its cultural influence in the world. Fast food as a western culture is starting to enter Indonesia through KFC (Kentucky Fried Chicken) products which have crispy fried chicken and currently very popular in Indonesia. KFC gives a new nuance to the culture of Indonesian society. The findings in this paper, specifically the existence of KFC which was produced through westernization, provide an illustration of the globalization process that entered Indonesia in the development of KFC's crispy fried chicken fast food as a means of transforming the idea of local Indonesian food. The idea of fast food, instant ingredients and flavored ingredients has been ingrained into the eating habits of Indonesians. Spreading global ideas represented by KFC then building new creations. This is reflected in not only the local menu influencing American fast food products, but local products also experiencing improvisation, which is occured a hybridization process between KFC products and Indonesian food culture.